2020
DOI: 10.22270/jddt.v10i3.4096
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Contents and Antioxidant Capacity of Aqueous Extract from Pituranthos scoparius (Coss. & Dur.) Growing in Algeria

Abstract: This study aims to estimate the total phenolics, flavonoids and tannins contents then to investigate both in vitro antioxidant capacity models of aqueous extract (AqE) from the stems of Pituranthos scoparius, growing in Algeria. Total polyphenol contents were determined using Folin Ciocalteu's reagent; flavonoids were quantified employing the AlCl3 and method tannins using haemoglobin precipitation test. The in vitro antioxidant property was assessed by DPPH-scavenging radical and lipid peroxidation assays. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Extracts of Pimpinella battandieri had the ability to precipitate hemolyzed blood from bovine samples [ 20 ]. An aqueous extract of Pituranthos scoparis bark precipitated hemoglobin from blood sample hemolysates [ 21 ]. In separate studies, extracts of Phlomis bovei De, Hertia cleirifolia , Cucumis melo , and Myrtus communis precipitated proteins in bovine blood [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracts of Pimpinella battandieri had the ability to precipitate hemolyzed blood from bovine samples [ 20 ]. An aqueous extract of Pituranthos scoparis bark precipitated hemoglobin from blood sample hemolysates [ 21 ]. In separate studies, extracts of Phlomis bovei De, Hertia cleirifolia , Cucumis melo , and Myrtus communis precipitated proteins in bovine blood [ 22 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We employed the vanillin assay to determine the condensed tannins in the extracts. Published research showed that red complexes result in the reaction of vanillin with the terminal flavonoid group of condensed tannins (CT), ( Karbab et al, 2020b ). Briefly, 1.5 mL of 4 % vanillin/methanol solution was added to 1 mL of extract.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-inflammatory assay of E. arborea extracts was examined in edematous induced by croton oil in mice according to Karbab et al (2019) and Karbab et al (2020a) . In the topical assay, mice were divided into 4 groups of 6 animals each.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidants are tremendously important substances which possess the ability to protect the body from damage caused by free radical induced oxidative stress (Almada-Taylor et al, 2018;Unal et al, 2022). Phenols and flavonoids form different origin include fruits, vegetables, and medicinal and aromatic plants, are phytoconstituents gaining reputation for their antioxidant abilities (Karbab et al, 2019;Phuyal et al, 2020;Uysal et al, 2021). These components are well known for a variety of therapeutic properties on health of human (Selamoglu, 2017a;Selamoglu, 2017b;Jiang et al, 2019;Selamoglu and Akalin, 2019).…”
Section: Introductionmentioning
confidence: 99%